"I am the character, the character is me": A thematic analysis of the user-avatar relationship in videogames. (June 2023) - Szolin, Kim; Kuss, Daria J.; Nuyens, Filip M.; Griffiths, Mark D.
Abstract: Far from merely being a tool to navigate a virtual world, individuals can often develop strong and complex relationships with their videogame characters. The present study examined the bond that can develop between a user and their avatar, as well as factors that can influence this relationship dynamic through the use of thematic analysis. Semi-structured interviews were carried out with 12 videogame players from the UK and US aged between 18 and 27 years. The results identified five major themes, comprising: (i) 'heterogeneity of game worlds'; (ii) 'avatar attachment'; (iii) 'game experiences affecting physical world behaviour and attitudes'; (iv) 'types of self in a virtual world' (with the sub-themes of 'actual self', 'idealised self', and 'utopian self'); and (v) 'game difficulty affecting user-avatar relationship'. The results showed gamers use their avatars as a means to insert a virtual version of themselves into the videogame or to attain a desired version of the self, sometimes including elements of fantasy. In addition, participants indicated that games with an advanced difficulty and avatar customisation appeared to facilitate stronger bonds to a character. Finally, several avenues of future research are discussed, in particular pertaining to the advancement of research relating to the Proteus effect. Highlights: Gamers can develop strong and complex relationships with their virtual world avatar. Avatars are used to create a different virtual versions of the user's self. Game difficulty and customisation options can affect the user-avatar relationship. Experiences in virtual worlds influence and impact a user in the physical world.